Systematic sources of sub-optimal interface design in large product development organizations - Grudin, Jonathan (DAIMI Report Series, 1990)
The need for the developers of interactive systems to understand the eventual users and their work is well known. The first part of this paper explores the underlying problems in achieving an understanding of computer users and their work in one systems development context: large product development organizations. The second part describes organizational goals that can conflict with good interface design. These goals often seem unrelated to interface considerations, but in the absence of knowledge of users and their work, they may be an unrecognized, subtle source of bad design decisions. While each organization is unique, the hope is that the forewarned reader will be better able to anticipate, recognize, and respond to these and similar challenges when they do appear.